Long-term outcome following lateral foraminotomy as treatment for canine degenerative lumbosacral stenosis - Andrade Gomes, Sergio; Lowrie, Mark; Targett, Mike (BMJ, 2018)
Lateral foraminotomy has been described as an effective surgical treatment for foraminal stenosis in the treatment of degenerative lumbosacral stenosis (DLSS) in dogs. Clinical records were reviewed from 45 dogs which had undergone lateral foraminotomy at the lumbosacral junction either alone or in combination with decompressive midline dorsal laminectomy. Short-term outcome at six weeks was assessed by the surgeon to be good (11.1 per cent) or excellent (88.9 per cent) in all 45 cases. Long-term outcome beyond six months for lumbosacral syndrome was assessed by the owner as excellent in all 34 cases for which follow-up was available despite recurrence in five cases. Recurrence of clinical signs was not related to re-establishment of foraminal compression at the surgical site when assessed on repeat MRI and was managed by either contralateral foraminotomy in one case or conservative management with excellent response. This study confirms lateral foraminotomy as an effective procedure in the management of DLSS-affected dogs suffering from foraminal stenosis and demonstrates that initial good short-term results are maintained long term despite some treatable recurrences. Lateral foraminotomy is an effective procedure when used appropriately in DLSS with foraminal stenosis either alone or in combination with midline dorsal laminectomy.